(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The implementation of International Financial Reporting Standards (IFRSs) will improve the internal management system of business entities through the use of uniform methods of accounting, provide information to stakeholders about the financial condition of the enterprise and increase the company’s competitiveness. This article illustrates the relevance of applying the IFRS to our national accounting system today.